Pembuatan Rencana Tata Kelola Dan Bimbingan Teknis Pengembangan Atraksi Wisata Camping Ground Desa Mekarsari Gambung Kabupaten Bandung - Gundur Leo; Sri Surjani Tjahjawati; Marceilla Suryana; Chandra Budhi Septyandi; Syifaa Novianti; Sherly Raka Siwi Putri Utomo; Rikantini Widiyanti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
This article describes the process and results of Community Service (PKM) activities carried out by the Bandung State Polytechnic in partnership with the Mekarsari Gambung Tourism Village, Bandung Regency manager. The PKM activity was carried out to solve governance problems and human resource problems faced by the Mekarsari Gambung Tourism Village. The Governance Plan document is prepared to serve as a guide for local tourism managers to increase the potential of tourist attractions and the competence of human resources in tourist villages. Furthermore, technical guidance (Bimtek) for the development of tourist attraction businesses is carried out to increase the capacity of the expertise and knowledge of the Mekarsari Gambung Tourism Village managers and the surrounding community so that they can be applied in efforts to develop the potential of tourism villages.